Impacts of the Clean Air Act on the Power Sector from 1938-1994: Anticipation and Adaptation - Karen Clay; Akshaya Jha; Joshua Lewis; Edson R. Severnini (Institute of Labor Economics (IZA), 2021)
The passage of landmark government regulation is often the culmination of evolving social pressure and incremental policy change. During this process, firms may preemptively adjust behavior in anticipation of impending regulation, making it difficult to quantify the overall economic impact of the legislation. This study leverages newly digitized data on the operation of virtually every fossil-fuel power plant in the United States from 1938-1994 to examine the economic impacts of the 1970 Clean Air Act (CAA) on the power sector. This unique long panel provides us an extended pre-regulation benchmark, allowing us to account for both anticipatory behavior by electric utilities in the years leading up to the Act's passage and reallocative effects of the CAA across plant vintages. We find that the CAA led to large and persistent decreases in output and productivity, but only for plants that opened before 1963. The timing aligns with the passage of the original 1963 CAA, which provided the federal government with the authority to "control" air pollution, sending a strong signal to firms of impending federal regulation. We provide historical evidence of anticipatory responses by utilities in the design and siting of plants that opened after 1963. We also find that the aggregate productivity losses of the CAA borne by the power sector were substantially mitigated by the reallocation of output from older less efficient power plants to newer plants.
Keywords: K32; N52; Q52; 330; power plants; electricity generation; total factor productivity; clean air act; air quality regulations; NAAQS